Metabolomic signature of type 1 diabetes-induced sensory loss and nerve damage in diabetic neuropathy - Rangel Rojas, Daniel; Kuner, Rohini; Agarwal, Nitin (Journal of molecular medicine, 2019)
Diabetic-induced peripheral neuropathy (DPN) is a highly complex and frequent diabetic late complication, which is manifested by prolonged hyperglycemia. However, the molecular mechanisms underlying the pathophysiology of nerve damage and sensory loss remain largely unclear. Recently, alteration in metabolic flux has gained attention as a basis for organ damage in diabetes; however, peripheral sensory neurons have not been adequately analyzed with respect to metabolic dysfunction. In the present study, we attempted to delineate the sequence of event occurring in alteration of metabolic pathways in relation to nerve damage and sensory loss. C57Bl6/j wild-type mice were analyzed longitudinally up to 22 weeks in the streptozotocin (STZ) model of type 1 diabetes. The progression of DPN was investigated by behavioral measurements of sensitivity to thermal and mechanical stimuli and quantitative morphological assessment of intraepidermal nerve fiber density. We employed a mass spectrometry-based screen to address alterations in levels of metabolites in peripheral sciatic nerve and amino acids in serum over several months post-STZ administration to elucidate metabolic dysfunction longitudinally in relation to sensory dysfunction. Although hyperglycemia and body weight changes occurred early, sensory loss and reduced intraepithelial branching of nociceptive nerves were only evident at 22 weeks post-STZ. The longitudinal metabolites screen in peripheral nerves demonstrated that compared with buffer-injected age-matched control mice, mice at 12 and 22 weeks post-STZ showed an early impairment the tricaoboxylic acid (TCA cycle), which is the main pathway of carbohydrate metabolism leading to energy generation. We found that levels of citric acid, ketoglutaric acid (2 KG), succinic acid, fumaric acid, and malic acid were observed to be significantly reduced in sciatic nerve at 22 weeks post-STZ. In addition, we also found the increase in levels of sorbitol and L-lactate in peripheral nerve from 12 weeks post-STZ injection. Amino acid screen in serum showed that the amino acids valine (Val), isoleucine (Ile), and leucine (Leu), grouped together as BCAA, increased more than twofold from 12 weeks post-STZ. Similarly, the levels of tyrosine (Tyr), asparagine (Asn), serine (Ser), histidine (His), alanine (Ala), and proline (Pro) showed progressive increase with progression of diabetes. Our results indicate that the impaired TCA cycle metabolites in peripheral nerve are the primary cause of shunting metabolic substrate to compensatory pathways, which leads to sensory nerve fiber loss in skin and contribute to onset and progression of peripheral neuropathy.
Gesehen am 13.11.2019